The Jews of Pinsk, 1506 to 1880 - Nadav, Mordekhai (Stanford studies in Jewish history and culture., 2008)
'The Jews of Pinsk, 1506-1880' is part of a major scholarly project about a small city in Eastern Europe where Jews were a majority of the population from the end of the 18th century.